Pemanfaatan E-Commerce Sebagai Strategi Pemulihan Ekonomi UMKM Pasca Pandemi: Studi Literature - Naja, Nadia Syahran; Mandala, Nesha Adelina; Agustini, Agustini; Bakhita, Rona Maulidia; Redjeki, Finny (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
This study aims to analyze the utilization of e-commerce as an economic recovery strategy for Micro, Small, and Medium Enterprises (MSMEs) after the COVID-19 pandemic through a literature review approach. A descriptive method is employed to understand the role of e-commerce in enhancing competitiveness and sustainability of MSMEs. The findings indicate that the use of digital platforms has successfully expanded market reach and increased revenue for MSMEs. However, challenges such as limited technological knowledge and resources hinder the optimalization of e-commerce potential. This research emphasizes the importance of developing human resource capacity and fostering collaboration between government, private sector, and local communities to support MSMEs in leveraging e-commerce. With adequate support, the utilization of e-commerce can not only enhance revenue but also create opportunities for innovation and long-term growth for MSMEs in an increasingly competitive digital era.